Identification of unique genomic signatures in patients with fibromyalgia and chronic pain - Gayatry Mohapatra; Fabien Dachet; Louis J. Coleman; Bruce Gillis; Frederick G. Behm (Scientific Reports, 2024)
Abstract Fibromyalgia (FM) is a chronic pain syndrome characterized by widespread pain. The pathophysiology of fibromyalgia is not clearly understood and there are no specific biomarkers available for accurate diagnosis. Here we define genomic signatures using high throughput RNA sequencing on 96 fibromyalgia and 93 control cases. Our findings revealed three major fibromyalgia-associated expression signatures. The first group included 43 patients with a signature enriched for gene expression associated with extracellular matrix and downregulation of RhoGDI signaling pathway. The second group included 30 patients and showed a profound reduction in the expression of inflammatory mediators with an increased expression of genes involved in the CLEAR signaling pathway. These results suggest defective tissue homeostasis associated with the extra-cellular matrix and cellular program that regulates lysosomal biogenesis and participates in macromolecule clearance in fibromyalgia. The third group of 17 FM patients showed overexpression of pathways that control acute inflammation and dysfunction of the global transcriptional process. The result of this study indicates that FM is a heterogeneous and complex disease. Further elucidation of these pathways will lead to the development of accurate diagnostic markers, and effective therapeutic options for fibromyalgia.